The Changing Relationship Between Labor and the State in Contemporary Capitalism. (February 2015) - Howell, Chris
Over the course of the past quarter century, paralleling the decline of organized labor, there has been a marked increase in the role of the state in the industrial relations of advanced capitalist societies. This has come both in the form of state activism in the reconstruction of institutions, and through the replacement of collective self-regulation by employer and labor organizations with legal regulation. Unsurprisingly, these developments have failed to encourage a renewal of trade union collective power, leaving workers increasingly insecure, dependent upon markets, and vulnerable to the vagaries of state power.